The Usefulness of the Lutheran Confessions in the African World - Randrianasolo, Joseph (Dialog, 2006)
The Malagasy Lutheran Church is one of the fastest growing churches in Africa. Maturing after having been seeded by Western missionaries, the confessional bond to Lutheran history is flowering differently within (1) the development of African contextual theologies and (2) ecumenical dynamics involving Lutherans and other Christian traditions.